Demystifying Writing: Strategies for Developing Better Writing (Journal of NELTA, 2022)
Students are often afraid of writing tasks, regardless of whether they are writing in their own native language or are second language writers. I share examples of my own writing experiences and struggles, and then I argue how writing can be demystiﬁ ed, offering some strategies towards advancing one’s writing skills: understanding writing, doing free writing, identifying writing weaknesses, practicing enormously, visualizing purpose and audience, revising writing, articulating writer’s own voice, obtaining feedback, reﬂecting on own writing, and embracing mimesis approach. I discuss the strategies drawing on ideas from renowned writing theorists, including Elbow (1998), Harris (2006), Vilardi and Chang (2009), and Adler-Kassner and Wardle (2016), etc. This paper is particularly relevant to early career ELT teachers to understand and demystify the student writing process; however, it might also be helpful for any academic level of students to advance their writing.